Juridical Analyst of Village Fund Management in Community Empowerment Based on The Regulation of The Regent of Labuhan Batu Selatan Number 9 Of 2022 From the Perspective of Fiqh Siyasah - Bahriansyah Putra Lubis; Syaddan Dintara Lubis (Warmadewa Press, 2024)
This research examines the legal management of village funds for community empowerment in Labuhan Batu Selatan, as regulated by Regent Regulation Number 9 of 2022, from a Fiqh Siyasah perspective. Village fund management aims to support the implementation of village governance and increase community empowerment. In a legal context, it is important to analyze how existing regulations govern distribution of village funds as well the extent to which these regulations are implemented effectively to achieve empowerment goals. Central and regional finances received by the district, namely in their distribution in every village, are distributed with a fair distribution of at least 10%. In this research, a qualitative method with a descriptive approach was used. The results of this study show that normatively and administratively the management of village funds is running well but is not optimal related to substance of empowerment in the Community. However, based on core aspects management, it does not fully reflect the true meaning of community empowerment, apart from that, several stakeholder functions have not been implemented optimally. Village fund management is only dominated by Village leaders as organizers paternalistic attitude of village communities causes them to be less responsive and uncaring completely entrust Administration of the village budget by the village head